The Roses [videorecording (DVD)] - McNamara, Tony (Director); Cumberbatch, Benedict, 1976-; Colman, Olivia; Samberg, Andy, 1978-; Janney, Allison; Bromilow, Belinda, 1975-; McKinnon, Kate, 1984-; Gatwa, Ncuti, 1992-; Mani, Sunita; Williams, PC; Shapiro, Theodore, 1971-; Hoffmeister, Florian, 1970-; et al. (Searchlight Pictures, 2025)
"Life seems easy for picture-perfect couple Ivy and Theo: successful careers, a loving marriage, great kids. But beneath the façade of their supposed ideal life, a storm is brewing. As Theo's career nose-dives while Ivy's own ambitions take off, a tinderbox of fierce competition and hidden resentment ignites in this wonderfully wry, dark comedy"--